2012
DOI: 10.1016/j.physletb.2011.12.064
|View full text |Cite
|
Sign up to set email alerts
|

On the Hamiltonian analysis of non-linear massive gravity

Abstract: In this paper we present a very simple and independent argument for the absence of the Boulware-Deser ghost in the recently proposed potentially ghost-free non-linear massive gravity. The limitation is that, in its simple form, the argument is, in a sense, non-constructive and less explicit than the standard approach. However, the formalism developed here may prove to be useful for discussing the formal aspects of the theory.Comment: 8 pages; minor changes; one of the references and the sign of the potential… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
76
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(76 citation statements)
references
References 27 publications
0
76
0
Order By: Relevance
“…However, it has been clearly demonstrated that the full nonlinear theory is free of the Boulware-Deser ghost to all orders beyond the decoupling limit. This has been shown by various authors both from a direct canonical analysis in ADM variables [634,655,[696][697][698][699][700] and in the Stückelberg and helicity language [701][702][703][704]. While this guarantees that the theory propagates only 5 degrees of freedom, even non-linearly, it nevertheless remains possible for one or more of these 5 physical modes to become ghostly around particular backgrounds, providing further constraints on the theory.…”
Section: Freedom From Ghostsmentioning
confidence: 82%
“…However, it has been clearly demonstrated that the full nonlinear theory is free of the Boulware-Deser ghost to all orders beyond the decoupling limit. This has been shown by various authors both from a direct canonical analysis in ADM variables [634,655,[696][697][698][699][700] and in the Stückelberg and helicity language [701][702][703][704]. While this guarantees that the theory propagates only 5 degrees of freedom, even non-linearly, it nevertheless remains possible for one or more of these 5 physical modes to become ghostly around particular backgrounds, providing further constraints on the theory.…”
Section: Freedom From Ghostsmentioning
confidence: 82%
“…This action also resembles the Polyakov action to some extent. Expressions similar to Lagrangian (A.5), with gravitons activated, have been utilized to re-confirm the absence of the BD ghost in ghost-free massive gravity [50,51]. Further integrating out λ ρσ , we arrive at To quadratic order in fluctuations, we then have…”
Section: Jhep04(2016)188mentioning
confidence: 99%
“…However, there is a direction in space of these variables along which there is no restriction at this level of Hamiltonian analysis [9]. It signals a spatial sector constraint.…”
Section: Non-perturbative Definition and Analysismentioning
confidence: 99%